PALYNOLOGY OF A RESIN FROM AN EGYPTIAN COFFIN OF THE 2ND-CENTURY BC (REVIEW OF PALAEOBOTANY AND PALYNOLOGY, 1992)
A palynological analysis was carried out on a small amount of resin from the inside of an anthropoid Egyptian stone coffin from the second century B.C. Pinus halepensis Miller is the best represented resiniferous plant (5.3%) in the pollen spectrum and the botanical origin of the resin can be ascribed to it. The only group of pollen which is relatively abundant in the spectrum is Poaceae (29.6%). This high percentage suggests that grasses were in bloom during the period the resin was collected (late spring or summer). Pollen of Quercus ilex. Olea europaea, Ostrya carpinifolia, Castanea sativa were also found. Pollen grains of Hordeum and Avena/Triticum types together with those of Plantago, Urtica, Chenopodiaceae, Rumex and Artemisia represent anthropogenic indicators. A phytogeographical interpretation of the found pollen assemblage suggests the eastern part of the Mediterranean as the most probable area where the resin was collected. The presence of Cedrus libani pollen suggests an origin from south-eastern Turkey, north-western Syria or northern Lebanon. The flora of this area is in accordance with the pollen assemblage found in the studied resin.
APS